2014
DOI: 10.1371/journal.pone.0104395
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Prostatic Urethral Angle with the Severity of Urinary Symptom and Peak Flow Rate in Men with Small Prostate Volume

Abstract: PurposeTo evaluate the effects of prostatic anatomical factors on male lower urinary tract symptoms (LUTS) and the peak flow rate (Qmax) in patients with small prostate volume (PV).Materials and MethodsRecords were obtained from a prospectively maintained database of first-visit men with LUTS. Patients whose total PV (TPV) was greater than 30 mL were excluded; 444 patients were enrolled in the study. The TPV, transitional zone volume (TZV), transitional zone index (TZI), intravesical prostatic protrusion (IPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Meanwhile, a higher bladder neck on cystourethroscopy is generally thought to be a causal factor of BOO and LUTS, and corresponds with increased PUA on TRUS. PUA is significantly associated with Q max and urinary symptom score in patients with LUTS/BPH, and its informative value seems to be more pronounced in men with LUTS and a small TPV [7,8]. Ku et al [9] maintained that PUA is a non-invasive method to assess BOO, although PUA was not associated with urinary symptoms and Q max in their patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, a higher bladder neck on cystourethroscopy is generally thought to be a causal factor of BOO and LUTS, and corresponds with increased PUA on TRUS. PUA is significantly associated with Q max and urinary symptom score in patients with LUTS/BPH, and its informative value seems to be more pronounced in men with LUTS and a small TPV [7,8]. Ku et al [9] maintained that PUA is a non-invasive method to assess BOO, although PUA was not associated with urinary symptoms and Q max in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting published evidence about whether the TZI is associated with urinary symptoms . During the last decade, there have been several reports on IPP and PUA . Chia et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, urodynamic findings showed that only half of the patients demonstrated bladder outlet obstruction in LUTS patients with a small prostate volume (PV), indicating the heterogeneity of this disease [ 3 ]. For this reason, several anatomical prostatic factors, such as the transitional zone index (TZI) and prostatic urethral angle (PUA), rather than simple volume parameters, have been investigated [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PUA determined with TRUS is the angle formed by two rays of the proximal and distal prostatic urethra on the midsagittal plane image. PUA is associated with urinary symptom severity and Qmax in men with LUTS and a small prostate volume 15. The correlation between PUA ≥35° and incidence of BOO was found to be significant in 260 men with LUTS/BPH 16.…”
Section: Rezūm® System – Convective Rf Water Vapor Thermal Therapymentioning
confidence: 90%